2021
DOI: 10.3832/ifor3640-014
|View full text |Cite
|
Sign up to set email alerts
|

Growth and physiological acclimation to shade in young plants of Adesmia bijuga Phil., a critically endangered species in central Chile

Abstract: Biogeosciences and Forestry Biogeosciences and ForestryGrowth and physiological acclimation to shade in young plants of Adesmia bijuga Phil., a critically endangered species in central Chile Marco A Yáñez (1) , Persy Gómez (2) , John Gajardo (3) , Sergio Espinoza (4) Adesmia bijuga Phil. is an endemic and endangered shrub species of central Chile. Its potential shade intolerance is one of the leading hypotheses for its vigor loss when the species grows beneath closed canopies. The objective of this study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…Similarly, Zhu et al [67] found that shoot weight is not affected by shade, while another study confirmed that plant biomass production is higher in 0% shade than in 60-90%-shaded plants [68]. Yanez et al's [69] findings are in line with ours, recording that half-shade and no-shade treatment lead to higher shoot and dry biomass than full shade. This is due to the decline in the photosynthetic capacity and change in enzyme activity [70].…”
Section: Effect Of Shadesupporting
confidence: 78%
“…Similarly, Zhu et al [67] found that shoot weight is not affected by shade, while another study confirmed that plant biomass production is higher in 0% shade than in 60-90%-shaded plants [68]. Yanez et al's [69] findings are in line with ours, recording that half-shade and no-shade treatment lead to higher shoot and dry biomass than full shade. This is due to the decline in the photosynthetic capacity and change in enzyme activity [70].…”
Section: Effect Of Shadesupporting
confidence: 78%